2021
DOI: 10.1002/eji.202149658
|View full text |Cite
|
Sign up to set email alerts
|

The unexpected contribution of conventional type 1 dendritic cells in driving antibody responses

Abstract: Antibodies are hallmarks of most effective vaccines. For successful T-dependent antibody responses, conventional dendritic cells (cDC) have been largely attributed the role of priming T cells. By contrast, follicular dendritic cells and macrophages have been seenas responsible for B cell activation, due to their strategic location within secondary lymphoid tissues and capacity to present native antigen to B cells. This review summarizes the mounting evidence that cDC can also present native antigen to B cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Our data indicate that samples with high antibody expression 21 days post-second vaccination maintained elevated antibody levels at 4 months. However, it’s important to note that this process predominantly occurs in the germinal centers (GC) of lymph nodes and not in the peripheral blood, hence it’s not depicted in Fig5. Direct B Cell Maturation Induction: Evidence suggests that DCs can directly induce B cell maturation through receptor CD40 [54], including instances where conventional DCs (cDCs) present antigens directly to B cells [55].
Figure 5: Dendritic Cells (DCs) and Their Role in Ribosome Complex Network-Mediated Antibody Production. This figure showcases the complex influence of dendritic cells (DCs) within the ribosome complex network on antibody secretion.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data indicate that samples with high antibody expression 21 days post-second vaccination maintained elevated antibody levels at 4 months. However, it’s important to note that this process predominantly occurs in the germinal centers (GC) of lymph nodes and not in the peripheral blood, hence it’s not depicted in Fig5. Direct B Cell Maturation Induction: Evidence suggests that DCs can directly induce B cell maturation through receptor CD40 [54], including instances where conventional DCs (cDCs) present antigens directly to B cells [55].
Figure 5: Dendritic Cells (DCs) and Their Role in Ribosome Complex Network-Mediated Antibody Production. This figure showcases the complex influence of dendritic cells (DCs) within the ribosome complex network on antibody secretion.
…”
Section: Resultsmentioning
confidence: 99%
“…4. Direct B Cell Maturation Induction: Evidence suggests that DCs can directly induce B cell maturation through receptor CD40 [54], including instances where conventional DCs (cDCs) present antigens directly to B cells [55].…”
Section: Result5: Possible Mechanism Of Dendritic Cells On Antibody P...mentioning
confidence: 99%
“… 35 , 36 Thus far, true FDCs have only been found in mammals and birds; however, it is increasingly apparent that some mammalian cDCs can present intact antigen. 37 Here, we sought to determine if any of the myeloid cells present in the nurse shark spleen might present intact antigen to facilitate B cell clonal selection.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Kinoshita et al reported murine data showing that the oral uptake of elderberry juice induced a dose-dependent stimulatory effect, leading to increased titers of virus-neutralizing antibodies in bronchoalveolar lavage fluids as well as in the serum of the treated mice [ 15 ]. Since DCs are also important for the activation of B cells and thus for the production of antibodies [ 20 ], it is conceivable to speculate that the here reported elderberry extract (EC15), and its fractions, that is, CPS, BOUND and UNBOUND, could also enhance antibody production against, for example, different viruses, in vivo.…”
Section: Discussionmentioning
confidence: 99%